Three-dimensional Electro-Fenton degradation for fulvic acids with Cu-Fe bimetallic aerogel-like carbon as particle electrode and catalyst: Electrode preparation, operation parameter optimization and mechanism. Issue 4 (August 2021) - Li, Mingran; Qin, Xia; Cui, Jiaxin; Guo, Rui; Guo, Chengrui; Wang, Ziyuan; Li, Tinghui
Abstract: In this study Cu-Fe bimetallic aerogel-like carbon based on sodium alginate (SA) was prepared as catalytic particle electrode by freeze-drying and carbonization process. The characterization indicates that Cu and Fe were loaded on the surface and inside SA-based biomass carbon (SAC) in the form of a zero-valent copper-iron alloy to form a Cu-Fe/Sodium alginate Carbon (Cu-Fe/SAC) particle electrode. After using a three-dimensional Electro-Fenton (3D-EF) system with the prepared particle electrode, the optimal experimental operating parameters for removal of fulvic acid (FA) were obtained as follows: voltage 2.5 V, pH 5.4, and catalyst dosage 4 g/L. A removal efficiency from 82.9% to 74.4% for FA was achieved in a wide pH range of 3–7. Comparison experimental results indicate that the 3D-EF system with bimetallic Cu-Fe/SAC as the catalytic particle electrode (CPE) has higher FA degradation rate and mineralization efficiency than two-dimensional Electro-Fenton (2D-EF) system, even higher than the 3D-EF system with Cu/SAC or Fe/SAC. Hydroxyl radicals (·OH) trapping experiments showed that the main contribution to FA degradation and mineralization in the 3D-EF system would be the ·OH radical produced by a heterogeneous Fenton-like reaction. The comparison and trapping experiment results indicate that the possible mechanism of the 3D-EF with Cu-Fe/SAC as CPE for FA degradation may involve adsorption, anode oxidation, heterogeneous and homogeneous Fenton-like reactions. Graphical Abstract: ga1 Highlights: A Cu-Fe/SAC catalytic particle electrode for 3D / EF system was prepared. Factors affecting FA degradation in 3D-EF systems were evaluated. Propose dynamic competition that may exist in 3D-EF system. The degradation of FA in 3D-EF system is mainly caused by ·OH.